(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The adoption rate of digital products and services has skyrocketed. As the user base grew, so did the volume of data and the need for knowledge. The trend towards storing and processing this influx of data has been upward. Technology has been steadily trending forward, and with that, storage space and computing power. However, typical spinning discs incur a delay in transmitting data to processing components since they are slower than the computer capability. There is a growing Processing - I/O performance gap that contributes to this lag. When it comes to processing large amounts of data, the CPU-I/O performance difference widens. The Processing - I/O performance gap may be reduced with the help of suggested active storage architecture. This study presents a test environment for investigating the effect on application performance.